1993
DOI: 10.1017/s0261127900000164
|View full text |Cite
|
Sign up to set email alerts
|

Sight, sound and ceremony in the chapel of Galeazzo Maria Sforza

Abstract: Bernardino Corio's late fifteenth-century history of Milan covers the city's past from its foundations to the collapse of the Sforza dynasty. Following the historiographic traditions established by Leonardo Bruni, its essential outlines are founded on careful use of sources and, for more recent events, contemporary memories and impressions. It is, however, also characterised by judicious revisionism and anecdotal invention. The careful reader always needs to ask why digressions have been included and what hidd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Moreover, in 1993 Evelyn Welch produced the damning evidence of the stabling records of 1476: they showed that Weerbeke shared four horses with one other singer, Compere shared three, but Josquin shared only two. 34 Welch remarked on this: 'Scholars have correctly noted that, as singers often relied on benefices, Josquin's low salary did not necessarily indicate a lower estimation of his talents. But in this impartial indicator, Josquin was still down at the bottom of the list.…”
mentioning
confidence: 99%
“…Moreover, in 1993 Evelyn Welch produced the damning evidence of the stabling records of 1476: they showed that Weerbeke shared four horses with one other singer, Compere shared three, but Josquin shared only two. 34 Welch remarked on this: 'Scholars have correctly noted that, as singers often relied on benefices, Josquin's low salary did not necessarily indicate a lower estimation of his talents. But in this impartial indicator, Josquin was still down at the bottom of the list.…”
mentioning
confidence: 99%